Biomechanical study of proximal femur for designing stems for total hip replacement - Solórzano W. (2020)
Innovative hip implants should be designed in accordance with biomechanical models of the proximal femur and take into account both body weight and muscle action in order to improve usability and biomimetic performance. This article proposes a finite element analysis of the proximal femur using both cortical and trabecular regions and employing transverse isotropic properties with standardized loads taken from active and young patients. Maximum principal stresses are plotted to show the mechanical behavior of the femur and grouped to evaluate stress shielding. Tsai-Wu and the maximum principal stress fields are useful for finding the areas more prone to failure and analyzing the influence of the stems on femoral mechanics. Other parameters, such as the stem material, absence of neck and osteotomy level, are explained. This paper is expected to provide a guide for designers and surgeons of femoral stems for assessing qualitatively and quantitatively the risks of stress shielding. © 2020 by the authors.